Association study of depressive symptoms and periodontitis in an obese population: Analysis based on NHANES data from 2009 to 2014. - Shuning Li; Jilun Liu; Rui Zhang; Jianfeng Dong (PLoS ONE)
Background Obesity, depressive symptoms, and periodontitis are major worldwide health concerns. Despite separate studies on both illnesses, no research has directly examined the link between depressive symptoms and periodontitis in obese people. Given the close correlation between obesity and chronic illnesses, as well as the possibility of a bidirectional impact between depressive symptoms and periodontitis, this study aims to investigate the link between depressive symptoms and periodontitis in an obese population. Methods This study analyzed data from the NHANES database (2009-2014), including 4,820 persons aged 30 years or older with a BMI over 30. The severity of periodontitis was assessed by clinical attachment loss and probing depth, while symptoms of depressive symptoms were measured using the PHQ-9 questionnaire. After gender, age, race, education, ratio of family income to poverty, sleep duration, diabetes, and cardiovascular illnesses were controlled for, the independent connection between depressive symptoms and periodontitis was investigated using multivariable logistic regression. Results The modified models indicated a significant negative correlation between depressive symptoms and periodontitis (effect size: -0.13, 95% CI: -0.24 to -0.01, p = 0.0266), indicating that depressive symptoms may operate as a protective factor against periodontitis. Interaction studies did not indicate substantial impact modification by factors like age, gender, or education level. Conclusion This study is the first investigation demonstrating a negative link between depressive symptoms and periodontitis in obese persons, indicating a significant interaction between mental health and dental health in this demographic. The results highlight the importance of comprehensive psychological and oral health care in obese individuals, providing a new avenue for future research and therapeutic applications.